The Role of Leadership in Improving Organizational Citizenship Behavior and Performance of Vocational High School (SMK) Teachers - Thamrin, Muhammad; Nursaid, Nursaid; Janah, Zahrotul; Qomariah, Nurul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The government's efforts to help vocational schools produce graduates who are superior and absorbed in the world of work continue to be made. One of them is the existence of the Center of Excellence (PK) Vocational School program. This program aims to enable graduates to be globally competitive and able to open up job opportunities through entrepreneurship. This research aims to determine and analyze the impact of teacher leadership on teacher OCB and teacher performance at Muhammadiyah Vocational Schools domiciled in Banyuwangi. All 345 vocational school teachers were used as the population. The total sample is known to be 184 teachers using the Slovin Formula. Descriptive statistics are used to find out information about respondents and research variables. Structural Equation Model (SEM) with WarpPLS 7.0. After analysis, the results are that: 1) leadership at SMK Muhammadiyah Banyuwangi has a positive influence on teacher performance; 2) organizational citizenship behavior possessed by teachers can improve teacher performance.